PERAN ZISWAF DALAM PEMBERDAYAAN MASYARAKAT MISKIN DI PROVINSI BANTEN - Hermawan, Dhany; Waluya, Atep Hendang (Al-Infaq: Jurnal Ekonomi Islam, 2019)
One contributor to poverty in non-food commodities is housing cost. In Banten Province, there are 2.81 percent of houses that are vulnerable but are habitable and there are 0.18 percent of houses that are not habitable. Whereas in Islam, home is one of the basic needs. In Islam itself, there are several solutions to overcome this problem. This study aims to determine the role of zakat, infaq, shodaqoh and waqf in the empowerment of the poor in Banten Province through the housing grant program of Koperasi Syariah Benteng Mikro Indonesia. This research is a field research with the method of collecting data is unstructured interviews. Data analysis techniques used in this study were data reduction, data presentation and conclusion drawing. This study found that zakat, infaq and shodaqoh managed by the Koperasi Syariah Benteng Mikro Indonesia have a role in empowering the poor. Koperasi Syariah Benteng Mikro Indonesia of Indonesia until 2018 has built 140 housing units that are habitable and is even suitable as a pilot so that the beneficiaries can be released from one of the factors that causing poverty in terms of housing costs. Funds for the construction of 40 houses are sourced from zakat, infaq and shodaqoh; while 100 houses are from "dana kebajikan". In accordance with Islamic law, there is no. waqf fund used in this program.